ASUPAN GIZI MAKRO DAN OBESITAS SENTRAL DENGAN KADAR ASAM URAT DARAH PADA PASIEN RAWAT JALAN DI POLI ENDOKRINRSUP PROF DR R.D KANDOU - Yohanis A. Tomastola; I Made Djendra; Yulfina Tadjimo (POLTEKKES KEMENKES MANADO, 2015)
Data from the Health Research 2013 North Sulawesi prevalence of central obesity rankssecond for the entire province in Indonesia, namely by 38%. This number increased from2007 as many as 31.5% (Riskesdas, 2013). Overweight or obesity is often associated withserum uric acid levels and is one of the risk factors of hyperuricemia. This study describesthe relationship between macro nutrient intake and central obesity with elevated uric acidlevels in patients at Poli Endocrine outpatient department of Prof. Dr. RD Kandou.This research is a descriptive observational using cross sectional design. Poli Endocrineimplemented in the department of Prof. Dr. RD Kandou in May 2014. The subjects werepatients Hyperurisemia, totaling 31 respondents are determined based on the formulahypothesis test for a population proportion, taken by Consecutif sampling.These results indicate that statistically not all macro-nutrient intake, central obesityassociated with uric acid levels, but subjects with elevated uric acid levels, twice as manyare those who have a protein and carbohydrate intake exceeds needs. Results of LogisticRegression Analysis using methods Backward shows that central obesity is more variableeffect on uric acid levels compared to the intake of macro-nutrients. Macro-nutrients andcentral obesity is a risk factor for elevated levels of uric acid.